Sex offending: causal theories to inform research, prevention, and treatment - Stinson, Jill D. (The law and public policy, 2008)
Methodological limitations of relevant research -- Biological theories -- Cognitive theories -- Behavioral theories -- Social learning theories -- Personality theories -- Evolutionary theories -- Integrative theories and models -- Multi-modal self-regulation theory : a new integration